Export wage premium for south Brazilian firms: Interaction between export, human capital, and export destination - Luiz Felipe Campos Fontes; Igor Granitoff; Silvio H. T. Tai (EconomiA, 2020)
This paper looks for evidence of learning-by-exporting effects on firms' average wages and its interaction with human capital level and export destination. This interaction allows us to test the hypothesis that a wage premium for exporting firms should mainly be found in firms employing high-skilled labor. The analysis is based on panel data for the 2010-2013 period and approximately 305,000 south Brazilian firms. We explore different times of entry into export market to use a fixed effects specification. Our results show that on average there are no learning-by-exporting effects on average wages for firms in our sample. However, when interacting firms export status with its human capital level, the effects turn out to be statistically significant. Finally, results suggest that the interaction between export gains and firms' human capital level is driven by firms exporting to developing countries. We explain this last result by the following mechanism. Low wage countries mainly produce low quality goods. Therefore, firms employing high skilled labor can differentiate their products and consequently escape from intense competition from these countries in the foreign market, obtaining higher export gains.
Keywords: 330